Antiarrhythmic drug-induced smell and taste disturbances: A case report and literature review. Issue 29 (July 2018) - Che, Xiaoru; Li, Yuandong; Fang, Yuanjian; Reis, Cesar; Wang, Huan
Abstract: Rationale: Metoprolol and amiodarone are common antiarrhythmic drugs used in clinics throughout the world. The taste and smell alterations induced by antiarrhythmic drugs remain uncommon throughout the world, with less than 10 reported cases. Patient concerns: In this case report, we describe a case of a 73-year-old female, diagnosed with arrhythmias, was treated for metoprolol. At the third week of metoprolol treatment, the patient noticed a qualitative change in her ability to smell, also called dysosmia. After the metoprolol was tapered, her ability to smell was recovered. However, her arrhythmia was getting worse and the patient was given amiodarone. After using amiodarone for about 2 weeks, the patient felt hypogeusia, or loss of taste sensation. Diagnoses: The patient was diagnosed as dysosmia and taste disturbance induced by the antiarrhythmic drugs. Interventions: After noticed the side effects of the antiarrhythmic drugs, we asked the patient to abandon the drugs and have a radiofrequency ablation. Outcomes: Her ability of smell and taste were recovered after withdrawing the antiarrhythmic drugs. Also, in the follow-up appointment, she reported no complaints of smell or taste anymore. Lessons: These rare sensory disorders induced by anti-arrhythmic drugs were less documented in past literature. Our case report describes a patient with an arrhythmia who suffered reversible dysosmia and hypogeusia after taking metoprolol and amiodarone, respectively. We conclude that smell and taste disorders should be made aware to patients during the anti-arrhythmic treatment, helping to promote the safety of patients and drug compliance.